2023
DOI: 10.3390/foods12061292
|View full text |Cite
|
Sign up to set email alerts
|

The Introduction of Allochthonous Olive Variety and Super High-Density System in the Abruzzo Region: A Study on Olive Oil Quality

Abstract: The transition to a sustainable economic and environmental management of olive oil sector needs to be implemented in both national and regional territories through the introduction and development of innovative growing systems and variety. In this study, the olive oil quality parameters of local and allochthonous varieties cultivated in different orchards located in the Abruzzo region (Italy), using traditional and super high-density systems, were analyzed. Frantene, Lecciana, Koroneiki, and a mix of Arbequina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…As suggested by Camposeo et al (2021) super high density planting systems are able to produce nutraceutical EVOOs rich in polyphenols compounds, as demonstrated with "Lecciana" that is the first olive cultivar of Italian descent suitable for super high-density orchards. A recent study by Flamminii et al (2023) conducted in the Abruzzo region examined allochthonous cultivars suitability for super high density systems and concluded that it is possible to obtain nutraceutical EVOOs comparable to traditional ones.…”
Section: The Innovation Imperativementioning
confidence: 99%
“…As suggested by Camposeo et al (2021) super high density planting systems are able to produce nutraceutical EVOOs rich in polyphenols compounds, as demonstrated with "Lecciana" that is the first olive cultivar of Italian descent suitable for super high-density orchards. A recent study by Flamminii et al (2023) conducted in the Abruzzo region examined allochthonous cultivars suitability for super high density systems and concluded that it is possible to obtain nutraceutical EVOOs comparable to traditional ones.…”
Section: The Innovation Imperativementioning
confidence: 99%